The Adaptability of Cervical Cancer Patients - Hermayanti, Yanti; Sutadi, Heriandi; Setyowati, Setyowati; Sabarinah, Sabarinah; Fitri, Siti Ulfah Rifa’atul (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The problems that arise in patients with cervical cancer are not only physical, but also include other aspects such as psychological, social, and spiritual. The ability of cervical cancer patients in dealing with these problems is very diverse and cannot be generalized. AIM: The purpose of this study was to identify the adaptability of cervical cancer sufferers to physical, psychological, social, and spiritual issues. METHODS: A cross-sectional design study was conducted in this study. The number of samples was 96 respondents from a referral hospital in Bandung, West Java. The adaptability instrument was developed by researchers to assess physical, psychological, social, and spiritual adaptability. Statistical data analysis used univariate analysis for adaptive ability variable. RESULTS: All components of adaptability were quite low, including general (14.6%), physical (2.1%), psychological (19.7%), social (27.1%), and spiritual (27.1%). CONCLUSION: Findings regarding factors that could affect the ability of adaptation are highly recommended. This is to determine the right type of intervention in helping adaptability of cervical cancer patients in various aspects so that patients can get the appropriate implementation from health workers.